Pattern mapping in shoe upper design - Chan, Jin Hao (2019)
Shoe upper wear and tear that caused by creases due to flexing of the foot is one of the most common shoe upper failures. In this project, the auxetic mechanical metamaterial is used as a type of “material” in the mapping of the shoe upper to mitigate the creases due to flexing of the foot. Auxetic mechanical metamaterials are generally known by their negative Poisson’s ratio, negative elasticity, and negative compressibility. These unusual mechanical properties of the auxetic structures were expected to react to the flexing of the foot. On the other hand, additive manufacturing, or rapid prototyping was used to fabricate the shoe upper as the auxetic structures are too complex to be fabricated using other conventional manufacturing processes. Rapid prototyping with a desktop 3D printer is also cost-effective and time-saving. As customization has become a trend in the footwear industry, in this project, customization of shape and size of shoe upper was done using 3D scanning and CAD modeling.